Spirometric Findings among School-Aged First Nations Children on a Reserve: A Pilot Study - Don D Sin; Heather M Sharpe; Robert L Cowie; SF Paul Man; on behalf of the Alberta Strategy to Help Manage Asthma (ASTHMA) Executive Committee (Canadian Respiratory Journal)
BACKGROUND: Asthma and chronic obstructive pulmonary disease (COPD) are increasing concerns for First Nations peoples in Canada. Although hospital utilization for asthma and COPD among First Nations peoples has been increasing, the prevalence of asthma or wheezing is comparable to national averages.